Subcortical morphological correlates of impaired clock drawing performance - Seidl, Ulrich; Hirjak, Dusan; Remmele, Barbara; Wolf, Robert Christian; Kaiser, Elmar; Schröder, Johannes; Thomann, Philipp (Neuroscience letters, 2012)
The objective of this study was to investigate the associations between clock drawing test (CDT) performance and subcortical brain morphology. Fifty-four participants (21 patients with Alzheimer's disease, 23 with mild cognitive impairment and 10 healthy controls) underwent neuropsychological assessment and high-resolution magnetic resonance imaging at 3T. CDT performance was related to volume and shape measurements of amygdala, caudate nucleus, hippocampus, nucleus accumbens, pallidum, putamen, and thalamus, respectively. Impaired CDT performance was correlated with alterations predominantly in the hippocampus bilaterally and in the right globus pallidus. These associations referred to regionally specific morphometric alterations rather than to global atrophy of the respective structures. Our findings support an involvement of subcortical brain regions in CDT performance.